Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD